A study on immunization practices of mothers with children under five years of age in government district hospital Kalaburagi - Rayee, Ashwini G.; Dhanwadkar, Sharanabasappa S.; Harshangi, Sandeep (International Journal of Contemporary Pediatrics, 2024)
Background: Vaccines are the most powerful, safe and cost-effective interventions to prevent major illnesses that contribute to child mortality in the country. Negative parental perceptions of vaccination are also an important barrier to childhood vaccination.so this study was taken up to determine the knowledge, attitudes and practices (KAP) of mothers with children under five years of age, which will help the policy makers in implementing the immunization programme in a better way, to achieve >85% coverage. Methods: A semi structured pre-validated questionnaire designed to assess the KAP about vaccination was administered to 360 mothers fulfilling the inclusion criteria. The KAP data between fully immunized and partially immunized/unimmunized children was compared. Results: In our study, out of 360 children, 183 (50.8%) children were fully immunized, 155 (43.1%) children were partially immunized and 22 (6.1%) children were seen unimmunized. Mothers were the main decision makers regarding vaccination of their children. Majority, 183 (50.3%) mothers identified vaccine preventable disease as polio. On comparing the KAP data between mothers of fully immunized children and mothers of partially immunized/unimmunized children, mothers of fully immunized children found to have favourable knowledge, attitudes, perceptions and practices towards vaccination. Conclusions: We found significant lacunae in the KAP of mothers towards childhood vaccination, especially among mothers of partially immunized and unimmunized children.so, health education is also an essential component that can go a long way in improving the prevailing scenario of immunization in our country.